Harnessing wind and solar PV system to build hybrid power system - S. S. Saswat; Suman Patra; Debani Prasad Mishra; Surender Reddy Salkuti; Rudra Narayan Senapati (Institute of Advanced Engineering and Science, 2021)
Electricity is the most important consideration for individual needs. Natural crossover power architecture using photovoltaic and wind is presented in this study, together with a Cuk direct current-direct current (DC-DC) converter, third phase inverter, and an inductors capacitors (LC) filter. Due to its natural disposal and availability in India, wind power and photovoltaics are ideal for the hybrid system. Hybrid power structures, on the other hand, reduce the risk of damage to equipment in sustainable stock storage since they have a higher electrical output. MATLAB Simulink was used to demonstrate this hybrid application. Before connecting the entire DC voltage frame with the main lattice of the power frame, blocks such as the wind model, PV model, Cuk converter, inverter, and LC channel are built individually. Information limitations for participating in varying levels of irradiance and variations in wind speed. The results show that the hybrid system has a considerably more reliable standard in terms of energy efficiency than an independent framework. Furthermore, the hybrid system's Cuk DC-DC converter, three-phase standard-based inverter, and LC channel can minimise power switching power.